유리체절제술 후 발생한 눈물막 및 안구표면장애에 대한 0.15% 히알루론산나트륨 점안액의 효과 - 최지호; 박영명; 정진구; 조남천; 유인천 (검안 및 콘택트렌즈 학회지, 20(1), 2021)
Purpose: To confirm the effect of 0.15% sodium hyaluronate on tear film and ocular surface disorders after vitrectomy surgery. Methods: The control group 19 patients and the test group 20 patients who underwent vitrectomy were enrolled. The control group took only antibiotics and steroids eye drops after surgery for 1 month, and the test group used 0.15% sodium hyaluronate eye drops for 2 months additionally. Ocular surface disease index (OSDI), tear film break-up time, Schirmer test, corneoconjunctival staining and meibomian gland seretion test were evaluated before surgery (baseline), 1 day, 1 week, 1 month, and 2 months after surgery. Results: There was significant difference between the control and trial group at 1 week in Schirmer test (p = 0.038). In OSDI, the score significantly increased until 2 months after vitrectomy in the control group (p = 0.021). However, the test group recovered at 2 month after surgery. In control group, TBUT showed significant decrease at 1 month (p = 0.022) and Schirmer test showed significant decrease at 2 months (p = 0.048) compared to the baseline, but there was no difference in the test group. Corneoconjunctival staining showed early increase and then progressive decreasing tendency at postoperative period in both groups, but there was a significant decrease of corneal staining at 2 months (p = 0.007) compared to the baseline only in the test group. Conclusions: Tear film and ocular surface disorders that occurred after vitrectomy worsen after surgery and then mostly recover. Postoperative 0.15% sodium hyaluronate instillation can alleviate the dry eye symptoms and is thought to contribute to early improvement of clinical findings. KCI Citation Count: 0